CRISPR-Associated Factor Csa3b Regulates CRISPR Adaptation and Cmr-Mediated RNA Interference in Sulfolobus islandicus - Ye, Qing; Zhao, Xueqiao; Liu, Jilin; Zeng, Zhifeng; Zhang, Zhufeng; Liu, Tao; Li, Yingjun; Han, Wenyuan; Peng, Nan (Frontiers in Microbiology, 2020)
Acquisition of spacers confers CRISPR-Cas system with the memories to defend against invading mobile genetic elements. We previously reported that the CRISPR-associated factor Csa3a triggers CRISPR adaptation in Sulfolobus islandicus. However, a feedback regulation of CRISPR adaptation remain unclear. Here, we show that another CRISPR-associated factor Csa3b binds a cyclic oligoadenylates (cOAs) analog (5’-CAAAA-3’) and mutation at the CARF domain of Csa3b reduce the binding affinity. Csa3b also binds the promoter of adaptation cas genes and the cOAs analog enhances their binding probably by allosteric regulation. Deletion of csa3b gene triggers spacer acquisition from both plasmid and viral DNA, indicating Csa3b acted as a repressor for CRISPR adaptation. Moreover, we also find Csa3b activates expression of subtype cmr-α and cmr-β genes according to the transcriptome data, and demonstrate Csa3b binds the promoters of cmr genes. Deletion of csa3b gene reduces Cmr-mediated RNA interference activity, indicating that Csa3b acts as a transcriptional activator for Cmr-mediated RNA interference. In summary, our findings reveal a novel pathway for regulation of CRISPR adaptation and CRISPR-Cmr RNA interference in S. islandicus. Our results also suggest a feedback repression of CRIPSR adaptation by Csa3b factor and the cOAs signal produced by Cmr complex at the CRISPR interference stage.